Public governance: balancing stakeholder power in a network society - Bovaird, Tony (2005)
The emergence of governance as a key concept in the public domain is relatively recent, although the concerns which it embraces are age-old. This article traces the evolution of the concept and maps the contours of its current position in public administration. It suggests that `governance' as a set of balancing mechanisms in a network society is still a contested concept, both in theory and in practice, but that there are already many attempts to delineate its dimensions more clearly and to assess how well it is being achieved in different contexts. Public governance principles are also being incorporated within legislation but there is a need for proportionality - such principles need to be weighed against cost-effectiveness considerations. It is still unclear whether we are moving to a future in which government remains the key player in public governance or whether we might move through `governance in the shadow of government' to self-organizing policy and service delivery systems - `governance without government'. - Reproduced.
Keywords: Public administration